EDUCATION FOUNDATION POUK TOMANG WEBSITE USING MACROMEDIA DREAMWEAVER MX - Ramses Sitorus; Cut Asiana Gemawaty, Skom., MMSi (Jurnal Sistem Informasi, 2003)
Everything has been more rapid because of technological developments, one of the Internet. Internet has made it easier - especially for ease of profitable Internet service users. Information is now so easy to obtain thanks to the Internet, education can use this technology for entering the competition in providing information about schools and education quality in it. With the proposed project, expected Tomang POUK Education Foundation which is engaged in education can also benefit.